Association Between Sociodemographic Variables, Healthy Habits, and Stress with Risk Scales for Liver Disease Associated with Metabolic Dysfunction - Ángel Arturo López-González; Emilio Martínez-Almoyna Rifá; Hernán Paublini Oliveira; Cristina Martorell Sánchez; Pedro Juan Tárraga López; José Ignacio Ramírez-Manent (Life)
Metabolic dysfunction-associated fatty liver disease (MAFLD) is the most common cause of chronic liver disease worldwide, with a multifactorial etiology. This study aims to evaluate the associations between various sociodemographic variables, healthy habits, and stress with risk scale values for MAFLD. Materials and Methods: A descriptive, cross-sectional study was conducted on 16,708 Spanish workers to assess how sociodemographic variables (age, gender, and socioeconomic status), healthy habits (smoking, Mediterranean diet adherence, and physical activity), and stress correlate with values from three MAFLD risk scales: fatty liver index (FLI), hepatic steatosis index (HSI), and lipid accumulation product (LAP). Results: All analyzed variables were associated with the values of the three MAFLD risk scales. Among them, the variables showing the strongest associations (represented by odds ratio values) were age and physical activity. Conclusions: The profile of an individual at higher risk of elevated MAFLD risk scale values is a male, aged 50 or older, belonging to lower socioeconomic levels (manual laborers), a smoker, sedentary, with low adherence to the Mediterranean diet, and with high stress scale scores.